37.8k views
4 votes
2(x + 6) + 4 = 12x - 6

User Villapx
by
5.3k points

1 Answer

1 vote

Answer:

exact form:


x=(11)/(5)

Decimal:


x=2.2

Mixed Number Form:


x=2(1)/(5)

Explanation:

simplify
2(x + 6) + 4


2(x + 6) + 4 = 12x - 6

Move all terms containing x to the left side of the equation.


-10x+1=-6

Move all terms not containing x to the right side of the equation.


-10x=-22

Divide each term by − 10 and simplify.


x=(11)/(5)

the result can be shown in multiple forms

Exact Form:
x=(11)/(5)

Decimal Form:
x=2.2

and Mixed Number Form:
x=2(1)/(5)

User MariaZ
by
4.9k points